The effect of functional electrical stimulation of the abdominal muscles on motor performance and activity of the trunk in patients with stroke: A pilot study - Summerton, Tarryn (Division of Physiotherapy, 2024)
Background: Significant improvements in functioning in general, and in gait performance specifically, have been found following the application of Functional Electrical Stimulation (FES) in the lower limbs in patients with stroke (1,2). Theoretically, FES could confer the same benefits if utilised on the trunk to activate the abdominal muscles. However, this is not well researched. Thus, the primary aim of this study was to establish, in participants with stroke, the effect of FES application to the abdominals and conventional physiotherapy, on trunk performance, general motor impairments, performance in Activities of Daily Living, health related quality of life scores and Physiological Cost Index scores. The secondary aims were to describe the treatment techniques used by physiotherapists treating stroke patients at the site of the study and to determine the most suitable placement (bilateral vs unilateral) of FES electrodes to activate external obliques (EO) for use in combination with abdominal exercises. Ethical approval and permission for the study was obtained from the Human Research Ethics Committee at the University of Cape Town and the Western Cape Department of Health. Study 1: Description of Conventional Physiotherapy Interventions for patients with Stroke admitted to a rehabilitation centre in the Western Cape Methods: Cross-sectional descriptive study was conducted among 10 physiotherapists employed by the rehabilitation centre. There were no exclusion criteria. A questionnaire was purposively developed for this study, using physiotherapy intervention activities listed in studies by Veerbeek et al. (3) and De Wit et al. (4). Participants completed the questionnaire individually with assistance from the researcher. Frequency Tables were used to describe the techniques that were most and least used and their frequency of use in the last two weeks. Descriptive statistics were used to describe characteristics of participants. Results: All physiotherapists (n=10) working at the centre participated. The mean number of years of experience was 11.3 years. The most used treatment activities for the upper limb and lower limb, were joint mobilisation (used 10 or more times by 5 out of 10 participants) and therapeutic positioning of the hemiplegic leg (used 10 or more times by 4 out of 10 participants) respectively. FES was only used by one physiotherapist in the upper and lower limb. Study 2: Determination of best placement of FES to the abdominal muscles Methods: An experimental study with a pre-test post-test design was conducted with 12 participants with stroke. Inclusion criteria. Inpatients between 21 and 70 years old, with first ever stroke in the last four months, who could sit independently, who could understand, read and speak English or Afrikaans and minimum level of education of Grade 10. Exclusion criteria: any other neurological conditions, Page viii of 256 uncontrolled epilepsy, healing wounds/poor skin condition, pacemakers or other implants, abnormalities on an ECG, pregnant women, cognitive impairments, receptive and global aphasia that could not give informed consent and failed sensory screening. Four electrode placements with two positions, were tested: Placement A (Superolateral from the umbilicus above the eleventh rib (5) and the eighth intercostal space) and Placement B (two cm superior and two cm medial to ASIS (6) and the eighth intercostal space) as either a bilateral placement (A1, B1) over both external obliques (EO) muscles or unilateral (A2, B2) placement over hemiplegic EO only. A two-dimensional (2D) ultrasound image was used to measure muscle thickness of EO and Transversus abdominus (TrA) at rest and then at five seconds, 30 seconds, one minute and five minutes of stimulation. Participants also completed a VAS (range 0-10) to determine comfort level with stimulation (with and without exercise) and to measure perceived stability and effort exerted with completing the exercise (with and without FES stimulation). Results: Average age was 50 years old, and two thirds of the participants had a right sided stroke. Of the four placements, placement A1 showed a significant difference for TrA at baseline, 5 seconds and 30 seconds (p=0.02). Placement B2 showed highest mean muscle thickness measurements for EO at 30 seconds (4.85mm) and one minute (4.76mm) but these were not significant (p=0.33). Placement A2 was most comfortable for use with exercise and stimulation (VAS= 7.75) and placement B2 provided most stability with exercise and stimulation (VAS= 7.92) and had the second highest median score (VAS= 7.6) for comfort with exercise combined with FES. Placement B1 was deemed the least comfortable to utilise with stimulation alone and when FES stimulation was combined with exercise. Study 3: The effect of FES-abdominals on trunk performance, function, energy expenditure and HRQoL (a pilot study) Methods: A Single blind experimental study with pre-test post- test design was used to assess the Impact of FES intervention. Inpatients at a state rehabilitation centre at time of the study who were between 21 and 70 years old, with first ever stroke in the last four months were included. The same exclusion criteria as Study 2 was used. Baseline measures included the Trunk impairment scale (TIS), Barthel index (BI), Rivermead Motor Assessment (RMA) and the European Quality of Life-5 Dimension questionnaire (EQ-5D-3L). The experimental group received conventional physiotherapy and FES applied to hemiplegic EO, for four weeks in week three of admission. The control group received conventional physiotherapy and placebo FES to their hemiplegic EO, for four weeks in total. from. A research assistant blinded to group allocation reassessed all participants at two-week intervals and four weeks post intervention (week 8) using the same outcome measures. An assessment of the physiological cost index of gait (PCI) was added at the end of the four-week intervention period and re-assessed again four weeks later. Page ix of 256 Results: Twelve participants were enrolled in the study but ten completed the study because two participants did not arrive for the last assessment. The scores of all participants were included in the final analysis. No significant differences were found between the two groups for TIS, RMA, BI and EQ5D-3L VAS at baseline, two weeks, four weeks and eight weeks. There was a significant difference found for PCI at four weeks (p=0.05) favouring the control group. No significant difference was found at eight weeks for PCI. Over time both groups improved with the intervention group showing higher increases in the TIS and RMA-LT over the intervention period within group, however this was not significant. Discussion: The findings from the description of physiotherapy intervention are mostly in keeping with literature (4). Only one physiotherapist utilised FES in the upper limb and in the lower limb, which is aligned with findings from a survey completed with physiotherapists and occupational therapists about use of FES in post-stroke treatment (7), suggesting that physiotherapists do not commonly use FES. Placement B2 was found to be the best position to utilise for the pilot study, based on change in muscle thickness measurements for both EO and TrA and VAS scores. Placement B2 was used in two other studies by Baek et al. (6) and Park et al. (8) however, unilateral placement was found to be preferable by the participants in these studies. The pilot study showed both FES in combination with conventional therapy and conventional therapy improve outcomes in clients with stroke, but one is not superior to the other as no significant treatment effect was found. However, an appropriately powered study would need to be conducted to determine if it is more effective in improving outcomes than conventional therapy alone. Conclusion: Our study provides a useful description of physiotherapy interventions, which is usually poorly described in the literature, and it was the first description of physiotherapy interventions provided to stroke clients in a South African context. Suitable electrode placement for FES application to be utilised in combination with abdominal exercises, was in keeping with previous studies using NMES application to the abdominals, however, participants in our study preferred a unilateral application. FES application to the abdominals used synchronously with physiotherapy intervention may be a promising intervention to improve trunk performance, motor impairments and ADL performance however the result of our small study suggests that this intervention is not better than conventional physiotherapy.